Screening and Treatment of Latent Tuberculosis: A Systematic Review of Current Evidence - Elekes, Stefan; Lowe, Morgan; Kenny, Ailbhe; Clarke, Sean; Eddershaw, Charlie; O'Driscoll, Michael; Thong, Lorraine (Trinity Student Medical Journal, 2021)
Introduction: Latent tuberculosis is an infection by the bacteria Mycobacterium tuberculosis where the individual affected does not have active infection or symptoms of tuberculosis infection. Individuals with latent tuberculosis infection (LTBI) remain asymptomatic and non-infectious until the bacteria become reactivated. The purpose of screening and treating LTBI is to prevent reactivation and active disease. The aim of this review is to examine the current screening criteria for LTBI, their validity, and specificity for diagnosis by looking at the currently accepted treatment options and the evidence that supports their efficacy. Methods: Articles for review were sourced from the academic databases EMBASE and PubMed. Results were screened using PICOS criteria looking at a population of latent TB infected patients screened using a variety of screening tools. Results: Initial database searches identified 476 articles. 19 articles fit the eligibility criteria and were included for analysis. Current screening procedures include the tuberculin skin test (TST), T-SPOT.TB, and QuantiFERON-TB (QFTGIT) tests. Evidence showed that the T-SPOT.TB was the most cost-effective test to perform although its accuracy is not as reliable as the IGRA. Treatment plans for those with LTBI are diverse and can be beneficial in a variety of settings. The most effective treatments include isoniazid for 6 or 9 months, rifampicin for 3 to 4 months and isoniazid and rifampicin for 3 to 4 months. Conclusion: Overall, IGRAs are the most reliable screening tests but are advised to be used in conjunction with TSTs as the TST alone has been determined to be less accurate. There are different treatment regimens, all of similar efficacy. Longer regimes were as effective than those of a shorter duration, but shorter regimes showed higher completion rates.